Hubungan Merokok, Obesitas, Konsumsi Alkohol dan Aktivitas Fisik dengan Kejadian Hipertensi pada Masyarakat yang Berkunjung di Puskesmas Alak Tahun 2021 - Petrus Apriandre Nubatonis; Yuliana Radja Riwu; Soleman Landi (Yayasan Literasi Sains Indonesia, 2024)
Hypertension or high blood pressure is a increased systolic blood presure exceeding 140 mmHg and diastolic blood pressure above 90 mmHg in two reading done at five minute intervals in a sufficiently relaxed and resting state. The aims of this study was to determine the relationship between smoking, obesity, alcohol consumption and physical activity and the incidence of hypertension in the working area of ​​the Alak Health Center, Kupang City. This type of study is an analytic survey research with a case-control approach. There were 112 samples with 56 case samples each and 56 control samples with a ratio of 1:1 and these samples was taken using simple random sampling. Data were obtained from interviews using a questionnaire with the chi-square statistical test with a significance level of α = 0.05 and an odds ratio value. The results showed that smoking (0.000) and physical activity (0.000) had a relationship with the incidence of hypertension. It is hoped that the Alak Health Center can play a role in providing counseling to the surrounding community about how to prevent hypertension and how to adopt a healthy lifestyle